Taxonomic and nomenclatural revision of Rubus L. (Rosaceae) in Iran - Salahi, Razieh; Afsharzadeh, Saeed; Sochor, Michal (Phytotaxa, 2025)
Rubus L. is a taxonomically intricate genus of flowering plants characterized by extensive hybridization, polyploidy, and facultative apomixis. This study aims to revise and update the taxonomy and nomenclature of Rubus in Iran, a region recognized for its rich but underexplored diversity. Utilizing recent biosystematic data from ploidy level estimation and DNA analyses, combined with extensive fieldwork across various ecological regions and herbarium studies, we identify four sexual species—R. dolichocarpus, R. ulmifolius (both diploids) and R. caesius, R. glandulosus (both tetraploids), and one frequent group of polyploid apomicts (R. ser. Discolores). Among these taxa, R. ulmifolius and R. caesius are widely distributed, while the others are found in northern Iran, mostly in the Hyrcanian forest ecoregion. Additionally, we document three rare taxa—R. ser. Hystrix, R. ser. Sylvatici, R. sect. Corylifolii, and two primary hybrids—R. dolichocarpus × R. glandulosus and R. caesius × R. ulmifolius. This contribution provides a comprehensive field guide with morphological descriptions, diagnostic characters, notes on nomenclature, distribution, and ecology, a determination key, and photographic documentation.